Fatty acid composition of the blue crab (Callinectes sapidus Rathbun, 1896) in the north eastern Mediterranean - (:unkn) unknown (ELSEVIER SCI LTD, 2004)
The fatty acid composition in muscle (claw and breast) and hepatopancreas of the Blue Crab (Callinectes sapidus) of the northeast Mediterranean were determined. Fatty acid compositions were analysed by gas chromatography. The results showed that the fatty acid profiles were significantly different between claw meat, breast meat and hepatopancreas of the crab. The percentage of total saturated fatty acids was higher in the hepatopancreas than in the claw or breast meats. The total n6 fatty acids were 8.61%, 7.80% and 5.34% in the hepatopancreas, claw meat and breast meat, respectively. The claw and breast meats contained significantly (P < 0.05) higher amounts of total n3 fatty acids than did the hepatopancreas. The n3/n6 fatty acids ratio was higher in the breast meat than in the claw meat or the hepatopancreas. It is concluded that claw and breast meat are good sources of n3 PUFAs. Therefore, the results suggest that claw and breast meat of the blue crab are appropriate for human health. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: blue crab; fatty acids; claw meat; breast meat; hepatopancreas; CHOLESTEROL; MEAT